Switching to Territorial Taxation: FDI Effects for Host-Countries of Foreign Subsidiaries - Carolin Holzmann; Thiess Büttner (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
The paper explores the effects of the switch to territorial taxation on outbound FDI. Rather than employing standard FDI statistics, the paper uses data which reports the location of the ultimate owner. We use a quasi-experimental approach that exploits the timing of reforms. In order to provide a counterfactual we employ synthetic-control methods. Our results document a substantial increase of Japanese FDI in Germany after the switch from worldwide to territorial taxation in Japan in 2009. In contrast, the switch in the UK in the same year is not found to exert any significant effects on investment of UK multinationals in Germany. These findings support the view that only the switch in relatively high-tax countries exerts FDI effects.
Keywords: H25; F23; 330; FDI; Dividend Exemption; Tax Competition; Synthetic Control Method